Perbedaan Pelayanan Pasien Peserta BPJS dengan Pasien Umum di Rumah Sakit Terakreditasi Paripurna: Differences in Services Between BPJS Patient Participants and General Patients in Fully Accredited Hospitals - Eloy, Noel; Sutarno, Sutarno; Adriano, Adriano (Jurnal Hukum dan Etika Kesehatan, 2026)
This study discusses the standards of health services provided by fully accredited hospitals for BPJS participants and general patients, as well as the legal responsibility of fully accredited hospitals for discrimination committed by health human resources against BPJS patients. The method used in this study is normative legal research, with research approaches namely the legislative approach, comparative approach, and conceptual approach. The method uses analytical techniques in the form of grammatical interpretation and systematic interpretation to be able to analyze the primary and secondary legal materials used in this study. The results of this study indicate that the Standards of Accredited Hospital Services for BPJS Participants and General Patients include providing humane treatment without discrimination, not being profit-oriented, emergency services without having to pay a down payment, optimizing patient recovery and safety, carrying out targeted and efficient medical actions, mutual cooperation and togetherness from various health professions, providing balanced information, providing protection for patients and health workers, providing psychological support to patients in need, and providing education  related to health and disease prevention. Hospital responsibilities are carried out based the provisions in the Article 29 paragraph (2) of the Hospital Law, Articles 1365 and 1366 of the Civil Code.